Systemic gene expression profiles according to pain types in individuals with chronic spinal cord injury. (April 2021) - Morrison, Debra; Arcese, Anthony A; Parrish, Janay; Gibbs, Katie; Beaufort, Andrew; Herman, Paige; Stein, Adam B; Bloom, Ona
Pain affects most individuals with traumatic spinal cord injury (SCI). Major pain types after SCI are neuropathic or nociceptive, often experienced concurrently. Pain after SCI may be refractory to treatments and negatively affects quality of life. Previously, we analyzed whole blood gene expression in individuals with chronic SCI compared to able-bodied (AB) individuals. Most participants with SCI reported pain (N = 19/28). Here, we examined gene expression of participants with SCI by pain status. Compared to AB, participants with SCI with pain had 468 differentially expressed (DE) genes; participants without pain had 564 DE genes (FDR < 0.05). Among DE genes distinct to participants with SCI with pain, Gene Ontology Biological Process (GOBP) analysis showed upregulated genes were enriched in categories related to T cell activation or inflammation; downregulated genes were enriched in categories related to protein proteolysis and catabolism. Although most participants with pain reported multiple pain types concurrently, we performed a preliminary comparison of gene expression by worst pain problem type. Compared to AB, participants with SCI who ranked neuropathic (N = 9) as worst had one distinct DE gene (TMEM156); participants who ranked nociceptive (N = 10) as worst had 61 distinct DE genes (FDR < 0.05). In the nociceptive group, the GOBP category with the lowest P-value identified among upregulated genes was "positive regulation of T cell activation"; among downregulated genes it was "receptor tyrosine kinase binding". An exploratory comparison of pain groups by principal components analysis also showed that the nociceptive group was enriched in T-cell related genes. A correlation analysis identified genes significantly correlated with pain intensity in the neuropathic or nociceptive groups (N = 145, 65, respectively, Pearson's correlation r > 0.8). While this pilot study highlights challenges of identifying gene expression profiles that correlate with specific types of pain in individuals with SCI, it suggests that T-cell signaling should be further investigated in this context.